The History of the Emergence and Development of Waqf Symbols in the Quran Manuscripts (based on Al-Muqaddimah al-Jazariyyah) - Nematov, Jahongir (Indonesian Journal Publisher, 2024)
Ancient mushas were devoid of special symbols. The reason is that the righteous predecessors did not feel the need for such signs in order to read the Holy Qur'an. Later, the scribes were allowed to use such symbols to facilitate the students. And this practice was carried out step by step (gradually). We will describe this history in this article